Immune cell phenotype and function patterns across the life course in individuals from rural Uganda - Nalwoga, Angela; Nakibuule, Marjorie; Roshan, Romin; Kwizera Mbonye, Moses; Miley, Wendell; Whitby, Denise; Newton, Robert; Rochford, Rosemary; Cose, Stephen (Frontiers in Immunology, 2024)
To determine the pattern of immune cell subsets across the life span in rural sub-Saharan Africa (SSA), and to set a reference standard for cell subsets amongst Africans, we characterised the major immune cell subsets in peripheral blood including T cells, B cells, monocytes, NK cells, neutrophils and eosinophils, in individuals aged 3 to 89 years from Uganda.Immune phenotypes were measured using both conventional flow cytometry in 72 individuals, and full spectrum flow cytometry in 80 individuals. Epstein-Barr virus (EBV) IFN-g T cell responses were quantified in 332 individuals using an ELISpot assay. Full blood counts of all study participants were also obtained.The percentages of central memory (TCM) and senescent CD4+ and CD8+ T cell subsets, effector memory (TEM) CD8+ T cells and neutrophils increased with increasing age. On the other hand, the percentages of naïve T (TN) and B (BN) cells, atypical B cells (BA), total lymphocytes, eosinophils and basophils decreased with increasing age. There was no change in CD4+ or CD8+ T effector memory RA (TEMRA) cells, exhausted T cells, NK cells and monocytes with age. Higher eosinophil and basophil percentages were observed in males compared to females. T cell function as measured by IFN-g responses to EBV increased with increasing age, peaking at 31-55 years.The percentages of cell subsets differ between individuals from SSA compared to those elsewhere, perhaps reflecting a different antigenic milieu. These results serve as a reference for normal values in this population.